(untitled) - Scott Barrett (Rome, 1995)
This paper is a contribution towards understanding when cooperation could improve on nationalistic policy, in what areas cooperation has already been manifested and the determinants of successful cooperation. Contrary to the allegory of the commons, this paper shows that cooperative outcomes can be sustained under certain circumstance. This is encouraging, although the paper also argues that copperation has not always been successful and identifies the features of certain problems-such as the number of countries sharing a resource-that help to explain why. While offering an analytical framework for examining cooperation, the paper also throws up a challenge. The chanlenge is to devise means for sustaining cooperation, even when the circumstances would seem not to support such an outcome.
Keywords: economic development - social aspects